Curtain walling: a study on maintenance aspect / Muziati Hanafiah Mohd Hanafiah - Mohd Hanafiah, Muziati Hanafiah (2001)
Rapid development in construction technology and the evolution of hightechnology architectural style in Malaysia are two contributing factors to the rising of curtain walling buildings in Malaysia. Curtain walling, which is a glass-clad building circling the whole building externally, which is also functions as building envelope shielding the internal area from external environmental factors. The crucial issues impacting the curtain walling are the environmental factors. Assessment on the environmental impacts, thus become a necessity when selecting types of materials to be used as curtain walling. Since curtain walling has become such intensive development, life cycle costing is a critical aspect that should be put into consideration. The specification of glass as curtain walling which allows natural light penetration into the internal sides of the building is the reason on why such material is chosen as building skin. Synchronisation of building material and ‘corporate’ image that reflecting the building functions are other reasons on why curtain walling system is being adopted, besides the practicality of the construction system.